2022
DOI: 10.3389/fgene.2022.942806
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Differential Proteomic Analysis at Seedling Stage by Induction of Heavy-Ion Beam Radiation in Wheat Seeds

Abstract: Novel genetic variations can be obtained by inducing mutations in the plant which help to achieve novel traits. The useful mutant can be obtained through radiation mutation in a short period which can be used as a new material to produce new varieties with high yield and good quality wheat. In this paper, the proteomic analysis of wheat treated with different doses of 12C and 7Li ion beam radiation at the seedling stage was carried out through a Tandem Mass Tag (TMT) tagging quantitative proteomic analysis pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Consistent with the physiological results, the transcription levels of genes related to antioxidant enzymes and peroxisome in adventitious buds also significantly changed after CIB irradiation (Figure 7). In the case of wheat irradiated by CIB and γ-rays, the proteomic data also showed significant changes in the genes or proteins of POD, CAT, APX, glutamate decarboxylase, delta-1-pyrroline-5-carboxylic acid synthase, and succinate semialdehyde dehydrogenase, in 5-day-old seedlings [43]. Taken together, the antioxidant system works synergistically to scavenge excess ROS and maintain normal growth under radiation damage stress.…”
Section: Cib-induced Oxidative Damage Response At Physiology and Mrna...mentioning
confidence: 84%
“…Consistent with the physiological results, the transcription levels of genes related to antioxidant enzymes and peroxisome in adventitious buds also significantly changed after CIB irradiation (Figure 7). In the case of wheat irradiated by CIB and γ-rays, the proteomic data also showed significant changes in the genes or proteins of POD, CAT, APX, glutamate decarboxylase, delta-1-pyrroline-5-carboxylic acid synthase, and succinate semialdehyde dehydrogenase, in 5-day-old seedlings [43]. Taken together, the antioxidant system works synergistically to scavenge excess ROS and maintain normal growth under radiation damage stress.…”
Section: Cib-induced Oxidative Damage Response At Physiology and Mrna...mentioning
confidence: 84%
“…Similarly, Yang et al observed significant growth inhibition in Arabidopsis primary root elongation, sprouting and survival under a dose of 1.5107 ions cm −2 , while Ya et al observed dose-dependent growth inhibition in rice seedlings under low-energy N + beam injection [ 44 , 113 ]. Research conducted by Yuqi Li et al showed that the use of 12 C and 7 Li ion beams on winter wheat ( Triticum aestivum ) seedlings led to a decrease in their seedling height and root length [ 127 ]. This was further corroborated by a study conducted by Fifika et al, which revealed that carbon ion beam treatment had a similar effect on the growth of rice seeds [ 128 ].…”
Section: The Function Of Ros In Plant Response To Ion Beammentioning
confidence: 99%
“…Furthermore, ion beam irradiation could also induce changes at the epigenetic levels, such as DNA methylation (Qian et al, 2010;Yu et al, 2011;Lima et al, 2014). The transcriptional and proteomic response of plants can differ due to the variety of plants and ion type (Xiong et al, 2020;Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%